"Lost virtually everything he had learned": Some thoughts on the impact of the pandemic on literacy and child development - Tomás, Débora Nogueira; Moreira, Maria Beatriz S.; Pacheco, Maria Eduarda Santos (Seven Editora, 2023)
This paper discusses the impacts of social isolation and remote learning on the school life of children in the literacy phase during the COVID-19 pandemic, in the years 2020 and 2021, in Brazil. From the contributions of Historical-Cultural Psychology, an analysis of how remote teaching impacted the process of school literacy was carried out, so we used as a methodological procedure the application of a questionnaire, elaborated through the Google Form, which was sent to family members/guardians who, during remote education, had children enrolled in the final years of Early Childhood Education and the initial grades of Elementary School I in the State of São Paulo. The questionnaire was completed in August 2002. And the results revealed that remote teaching harmed the process of literacy and school development, whose greatest impact is related to the delay and difficulty in the process of acquiring reading and writing. Child behaviors of loss of motivation and interest, as well as attentional difficulty and anxiety during the remote teaching process, were also evidenced. Another important factor was the fact that the lack of follow-up of students by those responsible for child care during such activities at home, brought reflections on the importance of valuing the school context, a social institution that shares and teaches the knowledge necessary for literacy and human development.DOI:https://doi.org/10.56238/emerrelcovid19-037